2002
DOI: 10.1007/bf02703832
|View full text |Cite
|
Sign up to set email alerts
|

Intervalence charge transfer transition in mixed valence complexes synthesised from RuIII(edta)- and FeII(CN)5-cores

Abstract: Intervalence charge transfer properties were studied for a set of mixed valence complexes incorporating Ru(III) and Fe(II)-centres linked by various saturated and unsaturated bridging ligands (BL). Studies reveal that degree of ground state electronic interaction and coupling between Ru(III) and Fe(II)-centres can be attenuated by changing the nature of the bridging ligand. Further, inclusion of the bridging ligand with interrupted π-electron system in a β-CD cavity initiate an optical electron transfer from F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This provides direct evidence of the color change with respect to temperature stimuli. The theory behind the color change can be elucidated using the IVCT mechanism and it is observed in compounds having mixed valence states in central metals [18,19]. WO30.33H2O has multiple valence states and they swap their oxidation states with each other by absorbing energy.…”
Section: Resultsmentioning
confidence: 99%
“…This provides direct evidence of the color change with respect to temperature stimuli. The theory behind the color change can be elucidated using the IVCT mechanism and it is observed in compounds having mixed valence states in central metals [18,19]. WO30.33H2O has multiple valence states and they swap their oxidation states with each other by absorbing energy.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that orbital overlap or some electronic delocalization must take place for the IT transition to occur, and the π-conjugated nature of the bridging ligand and its length can play an important role. 8 However, Kubiak et al reported IT charge transfer between two µ 3 -oxoruthenium acetate clusters bridged by hydrogen bonds from the isonicotinic acid residues present. 9 Before this report, Kaifer et al showed remarkable electronic coupling between two identical ferrocene moieties separated about 10 Å and only connected by four hydrogen bonds, this IT was spotted approximately at 1200 nm in the absorption spectra.…”
Section: Abbreviationsmentioning
confidence: 99%